Dismantling racism and white supremacy in public service institutions and society: contextualizing the discussion and introducing the symposium. Issue 2 (3rd April 2022) - McCandless, Sean; Blessett, Brandi
Abstract: The field of public administration has long resisted admitting an uncomfortable truth. Public administrattion is culpable in creating and maintaining racist, white supremacist policies and institutions through which Black, Indigenous, and other communities of color disproportionately experience prejudice and discrimination and, therefore, inequities and injustices throughout public services and society. However, few have been willing to have this difficult conversation. This Dialogue symposium seeks to contribute to this conversation, and this introduction both previews pieces in the symposium while also adding context to key concepts and discussions.